PENGOLAHAN LIMBAH PLASTIK MENJADI KERAJINAN YANG BERNILAI EKONOMIS DI DESA BATU BOLA/SIMATOHIR - Seri Asmaidah; Wasna Sakinah; Elan Putri Napoga Hrp; Anju Debora (Jurnal ADAM : Jurnal Pengabdian Masyarakat, 2022)
This community service was carried out in April in the village of Batu Bola/Simatohir, Angkola Julu District, Padang Sidimpuan City. This service aims to invite the people of the village of Batu Bola to manage plastic waste into a craft that is useful and has economic value, to reduce the impact of plastic waste on the environment. This service method is carried out by explaining the dangers and impacts of plastic waste to the environment to the community and teaching how to process plastic waste into a craft. According to participants, this activity is very helpful in reducing the amount of plastic waste. During the activity, the service was carried out in the form of counseling about the dangers of plastic waste and the importance of protecting the environment, as well as field actions by inviting and teaching how and processing plastic waste into a craft. After the service is complete, the community will know about processing plastic waste into useful crafts. This can be seen from the increase in their active role and enthusiasm in carrying out activities. The objectives to be achieved in this Community Service activity include: 1) to reduce plastic waste around the environment. The method used is about the goals and objectives of achieving the goals by starting with questions to them so that the questions will refer to the activities to be carried out.   Pengabdian masyarakat ini telah dilaksanakan pada bulan April di desa Batu Bola/Simatohir  Kec Angkola Julu Kota Padang Sidimpuan.Pengabdian  ini bertujuan untuk mengajak masyarakat  desa batu bola unutuk mengelola limbah plastik menjadi sebuah kerajinan yang bermanfaat serta bernilai ekonomis,untuk mengurangi dampak limbah plastik terhadap lingkungan. Metode pengabdian ini dilakukan dengan menjelaskan bahaya dan dampak limbah plastik bagi lingkungan kepada masyarakat dan mengajarkan cara pengolahan limbah plastik menjadi sebuah kerajinan. Menurut partisipan dengan adanya kegiatan ini sangat membantu untuk mengurangi banyaknya limbah plastik.Dalam kegiatan inisedikit banyaknya sudah mengurangi banyaknya limbah plastik di sekitar lingkungan.Selama berlangsungnya kegiatan, Pengabdian dilakukan dalam bentuk penyuluhan tentang bahaya limbah plastik dan pentingnya menjaga lingkungan, serta aksi lapangan dengan mengajak dan mengajarkan cara dan pengolahan limbah plastik menajadi sebuah kerajinan.Setelah pengabdian selesai,masyarakat jadi Tahu tentang pengolahan limbah plastik menjadi kerajinan yang bermanfaat. Hal ini dapat dilihat dari peningkatan peran aktif dan antusiasme mereka dalam melaksanakan kegiatan. Tujuan yang ingin dicapai dalam kegiatan Pengabdian Masyarakat ini di antara nya: 1) untuk mengurangilimbah plastik di sekitar lingkungan.